2002
DOI: 10.1046/j.1365-2311.2002.00426.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of meadow suitability on female behaviour in the alpine butterfly Parnassius smintheus

Abstract: Abstract. 1. Many butterfly populations persist in networks of naturally fragmented habitat patches. Movement and reproductive decisions made by adult females are critical to the persistence of these populations because colonisation of extinct habitat patches in the network requires emigration of fecund adult females from their natal meadow and their subsequent establishment in the extinct patch.2. Movement and oviposition behaviours of mated Parnassius smintheus females released in suitable meadows (a good-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 42 publications
2
44
0
Order By: Relevance
“…Research took place over 3 years (2006)(2007)(2008) in the alpine meadows of Jumpingpound Ridge, in Kananaskis Country, Alberta, Canada (50°57 0 N, 114°55 0 W), a series of meadows used for the long-term study of P. smintheus dynamics (e.g., Roland et al 2000;Fownes and Roland 2002;Roland and Matter 2007). Data were collected in two separate but ecologically similar meadows, one near the northern (G) and one near the southern (L) end of Jumpingpound Ridge (Fig.…”
Section: Study Site and Study Speciesmentioning
confidence: 99%
See 2 more Smart Citations
“…Research took place over 3 years (2006)(2007)(2008) in the alpine meadows of Jumpingpound Ridge, in Kananaskis Country, Alberta, Canada (50°57 0 N, 114°55 0 W), a series of meadows used for the long-term study of P. smintheus dynamics (e.g., Roland et al 2000;Fownes and Roland 2002;Roland and Matter 2007). Data were collected in two separate but ecologically similar meadows, one near the northern (G) and one near the southern (L) end of Jumpingpound Ridge (Fig.…”
Section: Study Site and Study Speciesmentioning
confidence: 99%
“…Parnassius smintheus is common in alpine meadows throughout the Rockies, but is limited to areas with a sufficient supply of its host plant, S. lanceolatum (Fownes and Roland 2002), and nectar flowers like Arnica spp., Senecio spp., Aster spp., and other large yellow or yellowcentered composites. The life-cycle of P. smintheus varies along the species' north-south range, and many of its details remain unknown.…”
Section: Study Site and Study Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…We assume that migrating females move according to the rules of correlated random walk both within habitat patches as well as in the surrounding matrix, though possibly with different parameter values in the habitat and the matrix. Correlated random walk models have been frequently used in butterfly studies (Odendaal et al 1989;Turchin 1991;Schultz and Crone 2001;Fownes and Roland 2002). In addition to the correlated random walk, we assume that individuals show edge-mediated behavior and bias their movements toward the habitat patch when close to patch boundary.…”
Section: Migrationmentioning
confidence: 99%
“…1), has demonstrated that movement (7)(8)(9) and gene flow (10,11) are severely limited by encroaching forests. These butterflies are restricted to open alpine meadows in the Rocky Mountains where their larval host plant, lance-leaved stonecrop, Sedum lanceolatum, and adult nectar resources are present (12). By monitoring the population size of P. smintheus over an 11-year interval in a series of alpine meadows, we determine whether population growth is most similar between meadows close to each other, suggesting that local dispersal synchronizes nearby populations, and identify the components of landscape that determine the degree of synchrony, in particular the effect of encroaching forest.…”
mentioning
confidence: 99%